Urban transmission of mosquito-borne flaviviruses – a review of the risk for humans in Vietnam - Thang Nguyen-Tien; Lundkvist, Å.; Lindahl, Johanna F. (Informa UK Limited, 2019)
Vietnam is a tropical country where mosquito-borne diseases are common. This review explores the transmission of mosquito-borne flaviviruses in urban areas of Vietnam. It concludes that urban transmission has mainly been studied for Dengue virus, and so far, much less for Japanese encephalitis virus. Dengue is the most common flavivirus in Vietnam. Due to fast urbanization and favorable climatic conditions, the viral transmission concentrates mainly to large cities with high population density including Ha Noi, Nha Trang and Ho Chi Minh. Human cases of Japanese encephalitis have been controlled by an expanded immunization program. However, this virus is still circulating throughout the country, also in cities due to the pig rearing practices in urban and peri-urban areas. Zika virus is an additional major concern because it has long circulated in the Northern area and is now increasingly diagnosed in urban areas of the Central, Central Highlands and Southern regions using the same mosquito vectors as Dengue virus. There was alarge outbreak of Zika disease from 2016 to early 2017, with most infections observed in Ho Chi Minh city, the largest town in Vietnam. Other flaviviruses circulate in Vietnam but have not been investigated in terms of urban transmission.